Pembiasaan Membaca Surat-Surat Pendek Sebelum Pembelajaran PAI dalam Membentuk Karakter Kedisiplinan Siswa - Yulianasari, Cantika; Rahman, Abdul (An-Nuha, 2025)
The habit of reading short verses of the Qur'an before learning Islamic Religious Education is one of the effective educational methods to shape a child's personality until he/she is an adult. The implementation of the program of habituation of reading short verses can shape the character of disciplined students at SDN Ngaliyan 01 Semarang. Through this study, the discussion will focus on how the implementation of the program of habituation of reading short verses can shape a disciplined, religious, and moral character. The efforts of Islamic Religious Education teachers in maintaining consistent habits through WhatsApp groups will help students achieve learning success and shape good character in terms of being religious, moral, and disciplined.